Trends in adult physical fitness in China: an analysis of national monitoring reports (2000–2020) - Hang, Huabin (Frontiers in Sports and Active Living, 2025)
Background/ObjectivesTo summarize the results of China's five national monitoring reports (CFNMR) on physical fitness (PF) for adults. The Government of China has taken a systematic administrative approach to a creative environment building, and has conducted five national physical fitness monitoring, with a sixth already started in 2024.MethodsCFNMR included indices, rates, test indicators, and questionnaire indicators collected between 2000 and September 2024. Data were collected (every 5 years), analyzed (every 3 years) and published (government announcements and reports) by the Monitoring Center of the General Administration of Sport of China. Adults’ data were divided into Group A (20–39 years) and Group B (40–59 years). In this study, once the database was established using government reports as the standard, the indicators were categorized, counted, and descriptively analyzed using EXCEL.ResultsGroup A: Indices fluctuated up 2.98 (2010 highest 102.98), and rates fluctuated up 2.40% (2005 highest 89.3%). Group B: Indices continued to decline 0.23 (2014 lowest 99.77), and rates fluctuated up 3.00% (2019 highest 90.6%). Test and questionnaire indicators show different structural characteristics, but obesity (7.33%) and overweight rates (5.88%) continue to increase.ConclusionAdult physical fitness is improving, but physical activity is decreasing. The results of the overall growth shown by the tested indicators do not, however, represent the formation of well-functioning mechanisms. Obesity is an ongoing and growing problem that requires constant attention. It should consider adding a physical literacy monitoring component, utilizing public goods attributes, to promote sustainable change and reach more adults.